Forecasting exchange rates with commodity prices: A global country analysis - Martin Baumgärtner; Jens Klose (Philipps-University Marburg, School of Business and Economics, 2018)
This paper investigates the predictive properties of import and export prices of commodities on the exchange rates. A period from 1993 to 2016 is considered. We _nd that forecasts of the exchange rate adding commodity export and import prices are superior to those neglecting these variables. This holds irrespective of whether the countries are net exporters or importers of commodities. However, the forecasting power was even better in the 1990s and seems to have decreased since that that time. Nevertheless forecasts can even today be improved considerably by adding commodity prices.
Keywords: F17; F31; F47; C23; 330; Exchange Rate; Commodity Prices; Forecast; Panel-Analysis